Features of the Use of Competence-Based Approach in the Selection of Managers for the Trade - Larisa Grigorievna Desfontaines (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article focuses on the requirements of a modern manager with the positions of the competence approach. Describes in detail the characteristics of the personality of the Manager, which are necessary for the effective management of commercial organization. Explores the positive side of the standards of competence and disadvantages of the approach. The most common mistakes managers and their causes.